Data and code from: Spring phenological escape is critical for the survival of temperate tree seedlings - Lee, Benjamin; Ibanez, Ines (Dryad, 2021)
Understory plants in deciduous forests often rely on access to
ephemeral light availability before the canopy closes in spring and after
the canopy reopens in fall, a strategy commonly referred to as
phenological escape. Although there is evidence for a relationship between
understory plant phenology and demographic performance, a mechanistic link
is still missing. In this study, we bridged this gap by estimating annual
carbon assimilation as a function of foliar phenology and photosynthetic
capacity for seedlings of two temperate tree species that commonly
co-occur across eastern North America. We then modeled the relationship
between estimated carbon assimilation and observed seedling survival and
growth. Our results indicate that seedlings of both species strongly
depend on spring phenological escape to assimilate the majority of their
annual carbon budget and that this mechanism significantly affects their
likelihood of survival (but not growth). Foliar desiccation also played a
strong role in driving patterns of seedling survival, suggesting that
water availability will also help shape seedling recruitment dynamics. We
found only weak associations between seedling senescence in fall and
annual carbon assimilation, suggesting that phenological escape in fall
plays a relatively minor role in seedling demographic performance. Our
results indicate that spring phenological escape is critical for survival
of these temperate tree species, and thus any changes to this dynamic
associated with climate change could strongly impact these species’
recruitment.
These data were collected between 2014-2019 by Benjamin
R. Lee and include model code for the photosynthesis, survival, and growth
models outlined in the corresponding article. Models were conducted in
OpenBUGS which is free to download online. Data for all models are
included in the code documents in collapsible data-frames that are clearly
labeled. Initial values are also recorded at the bottom of each model.
Posterior parameter estimates are available in the supplemental materials
of the corresponding article.
All models were run separately for each species. Parameter definitions for
the photosynthesis model are provided in the supplemental materials for
this article along with an in-depth description of the model
structure.  Curve-level variables for photosynthesis models:
plant = individual replicate identifier, curveid = individual curve
replicate identifier, AQ = 1 indicates ACi curve and 2 indicates AQ curve,
PS = centered soil moisture value (see notes on soil moisture sub-model in
supplement), VS = centered Vapor pressure deficit values.
Observation-level variables for photosynthesis models: curve =
curve identifier (same as curveid above), Obs = individual gas exchange
measurement (multiple in each curve), Aobs = observed photosynthetic rate
(A), Q = light level (PPFD) inside the cuvette, Pressure = atmospheric
pressure, CiP = interstitial pressure, O = partial pressure of O2
Survival/growth model variables: Site = (1 = George
Reserve, 2 = Radrick Forest, 3 = Saginaw), surv = recorded as either alive
(1) or dead (0), growth = centered annual growth value, AnnC = centered
estimate of annual carbon assimilation, PctDam = percent of leaf recorded
as damaged by end of growing season, Des = binary desiccation
damage indicator (1 = present, 0 = absent), Deer = binary deer herbivory
indicator (1 = present, 0 = absent), SdlgA = individual identifier for
Acer seedlings, SdlgQ = individual identifier for Quercus seedlings, Year
starts at 1 indicating data collected in 2015, GSF = Global Site Factor
(centered around mean), Cohort = Seedling cohort (1-3 = seedlings planted
in 2014-2016, respectively), Age = age of seedling in years at time of
measurement
Keywords: Acer saccharum Marshall; Quercus rubra L.; foliar phenology; carbon assimilation; tree seedling growth; desiccation; C3 photosynthesis